2002
DOI: 10.1105/tpc.004028
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Transgene Silencing by Matrix Attachment Regions in Maize

Abstract: Matrix attachment regions (MARs) are DNA sequences that bind an internal nuclear network of nonhistone proteins called the nuclear matrix. Thus, they may define discrete gene-containing chromatin loops in vivo. We have studied the effects of flanking transgenes with MARs on transgene expression levels in maize callus and in transformed maize plants. Three MAR elements, two from maize ( Adh1 5 MAR and Mha1 5 MAR) and one from yeast (ARS1), had very different effects on transgene expression that bore no relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
29
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 82 publications
7
29
0
Order By: Relevance
“…However, it was not possible for Mankin and coworkers to determine if these increases in expression were due to greater proportions of expressing cells, cells expressing at higher levels, or both. Our data are in agreement with those of Brouwer et al (2002) and Mankin et al (2003), in that when MARs are incorporated into transgene constructs, we see an increase in the likelihood of expression. However, in contrast with Brouwer et al (2002), we observe that the expressing cells in lines transformed DNA was isolated from liquid cultures initiated from callus sectors ( Figure 6A, right column).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, it was not possible for Mankin and coworkers to determine if these increases in expression were due to greater proportions of expressing cells, cells expressing at higher levels, or both. Our data are in agreement with those of Brouwer et al (2002) and Mankin et al (2003), in that when MARs are incorporated into transgene constructs, we see an increase in the likelihood of expression. However, in contrast with Brouwer et al (2002), we observe that the expressing cells in lines transformed DNA was isolated from liquid cultures initiated from callus sectors ( Figure 6A, right column).…”
Section: Discussionsupporting
confidence: 93%
“…The authors noted fewer nonexpressing lines among lines that contained either the yeast (Saccharomyces cerevisiae) ARS1 MAR or the maize Adh1 59 MAR than among control lines. Based on these observations, they suggested that MARs increase the likelihood that an integrated gene will be expressed but not the level of expression (Brouwer et al, 2002). Mankin et al (2003) observed a similar MAR-induced reduction in the frequency of low expressing tobacco cell lines, but also noted that when these low expressing cell lines were removed from the analysis, MAR lines still showed an increase in GUS expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current assays for boundary element efficacy and the potential protection against gene silencing require the comparison of different constructs at different integration sites in large populations of plants or cells. Therefore, boundary action may be confounded with parameters beyond experimental control, such as different spectra of integration sites, complex integrations, boundary-transgene interactions, and boundary-plant species interactions (Brouwer et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The site where this chromatin fibers bind to matrix protein is called S/MAR [8,10]. Interaction between S/MAR and matrix protein causes the formation of a distinct loop domain which localize gene transcription units and specific regulatory elements to regulate transcription [4,11].…”
Section: Introductionmentioning
confidence: 99%